2013
DOI: 10.1155/2013/570946
|View full text |Cite
|
Sign up to set email alerts
|

Novel Evolutionary Models and Periodic Charts in p- and q-Individual Chromosomes of Auxiliary Lymph Node and Buccal Cells

Abstract: Signal copy number (SCN) and signal intensity (SI) of subtelomeres (ST) are investigated in auxiliary lymph node (ALN) and buccal (BUC) cells by fluorescence in situ hybridization. The extracted total cell of 38256 and 2309 was, respectively, analyzed from the benign ALN- and BUC-cells of an affected breast cancer patient. The Periodic model was based on ST behavior including normal-, down-, and upregulated clones with diverse SCN. The arm-p/q ratio based signature, as a subtelomeric array, reflects discordanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Heterogeneity of Telomere length, reflects the cellular evolution, at genomic and somatic level 19,[43][44][45] . Evolutionary hypothesis of TL, was initially unveiled in primary BC and brain tumors (BT) to provide an unique marker for cancer clinical management including prognosis, prediction and planning for an early detection by the circulating tumor cell (CTCs).…”
Section: Heterogeneity In Telomere Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterogeneity of Telomere length, reflects the cellular evolution, at genomic and somatic level 19,[43][44][45] . Evolutionary hypothesis of TL, was initially unveiled in primary BC and brain tumors (BT) to provide an unique marker for cancer clinical management including prognosis, prediction and planning for an early detection by the circulating tumor cell (CTCs).…”
Section: Heterogeneity In Telomere Lengthmentioning
confidence: 99%
“…Analysis with all probes showed that cells with positive signals correspond to 11.21% (4506/40.197) for ALN and 28.43% (2415/8494) for unaffected genomic cells. Adapted from: 45 Two cell populations, including normal and abnormal cells, were analyzed in order to assess their heterogeneity. The SCN and SI of FISH were used to characterize the STs presence in each or all chromosomes and to distinguish the p and q arms.…”
Section: Sub-telomeric Signals Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported a different profile of FISH signal, which reflects a distinct copy number of ST sequences of buccal and ALN cells and provides a personalized signature for the progress of breast neoplasm (Mehdipour et al, ). Given this personalized insight, the aim of the present study was to analyze the ST profiles for distribution of hybridization signals and intensity of individual p and q Chr arms in non‐affected (genomic) and ALN cells of a female patient previously affected by primary proliferative ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%